Leader of the Pack: Academic Giftedness and Leadership in Early Adolescence. Issue 4 (November 2019) - Peairs, Kristen F.; Sheppard, Christopher S.; Putallaz, Martha; Costanzo, Philip R.
The present study expanded our current understanding of leadership among academically gifted seventh-grade students by examining peer-identified leaders of naturally occurring social groups in a mixed ability setting. Three consecutive cohorts of seventh-grade students ( N = 474; 57% female; 43% European American) attending a public magnet secondary school participated. Results indicated that gifted students were more apt to be identified as leaders than nongifted youth and both conventional and unconventional styles of leadership related similarly to higher social standing and influence in the peer network. Nongifted leaders displayed a mixed profile of prosocial and more risky deviant behavior, whereas gifted leaders displayed a primarily prosocial leadership style. However, gifted leaders perceived themselves to be more influential and intimidating than other students and also endorsed sensation seeking tendencies more than other students. Findings underscore the heterogeneity of leadership during young adolescence and the distinct profile of gifted leaders compared with other leaders and gifted peers.